The role of organisational behaviour, leadership style, and work discipline in staff performance - Bangun, Rejeki (Institute of Computer Science (IOCS), 2024)
Human resource management is a very interesting topic to research because it influences the progress of an organisation. This research is to get information about organisation behaviour, leadership style, and work discipline and three factors affecting staff performance. This research used a questionnaire for 111 respondents and SPSS version 25. This Research is quantitative research and statistical analysis. Multiple linear regression method with quantitative analysis. Based on SPSS data analysis, the researcher got the result of multiple linear regression analysis for organisation behaviour (X1) is 2.721 with a significant 0.008, leadership style (X2) is 3.105 with a significant 0.002, and work discipline (X3) is 3.520 with a significant 0.001. The result of the simultaneous test (F test) was 32.249 with significancy 0.000. Conclusion for this research, the first hypothesis is that organisation behaviour has an influence on staff performance, the second hypothesis is that leadership style has an influence on staff performance and third hypothesis work discipline has an influence on staff performance, and the last hypothesis is that these three variables (organisation behaviour, leadership style, and work discipline) have simultaneous influence in staff performance